Integrated electrochemical and chemical system for ampere-level production of terephthalic acid alternatives and hydrogen - Lin Chen; Chang Yu; Xuedan Song; Junting Dong; Jiawei Mu; Jieshan Qiu (Nature Communications, 2024)
Abstract 2,5-Furandicarboxylic acid (FDCA), a critical polymer platform molecule that can potentially replace terephthalic acid, coupled hydrogen coproduction holds great prospects via electrolysis. However, the electrosynthesis of FDCA faces challenges in product separation from complex electrolytes and unclear electrochemical and nonelectrochemical reactions during the 5-hydroxymethylfurfural (HMF) oxidation. Herein, an electrochemical/chemical integrated system of alkaline HMF-H2O co-electrolysis is proposed, achieving distillation-free synthesis of high-purity FDCA by acidic separation/purification and hydrogen coproduction. This system achieves ampere-level current densities of 812 and 1290 mA cm−2 at potentials of 1.50 and 1.60 V, with nearly 100% FDCA yield and HMF conversion in only 6 min at 1.50 V. The electrooxidation of HMF involves a coupling of electrochemical and nonelectrochemical reactions, wherein the aldehyde group is dehydrogenated and oxidized, followed by dehydrated and oxidized of the hydroxyl group, ultimately forming FDCA. Concurrently, nonelectrochemical reactions of intermolecular electron transfer occur in HMF and aldehyde group-containing intermediates.